Serotonylation: Serotonin Signaling and Epigenetics - Bader, Michael (Frontiers in Molecular Neuroscience, 2019)
Serotonylation, the covalent linkage of serotonin to proteins has been discovered more than 60 years ago but only recently the mechanisms and first functions have been elucidated. It has been found that transglutaminases (TGM) such as TGM2 and the blood coagulation factor XIIIa are the enzymes which catalyze the linkage of serotonin and other monoamines to distinct glutamine residues of target proteins. The first target proteins, small G-proteins and extracellular matrix constituents, were found in platelets and are pivotally involved in platelet aggregation and the formation of thrombi. The serotonylation of the same proteins is also involved in insulin secretion and in the proliferation of pulmonary vascular smooth muscle cells and thereby in the pathogenesis of pulmonary arterial hypertension. Recently histones have been described as targets of serotonylation opening the area of transcriptional control to this posttranslational protein modification. Future studies will certainly reveal further target proteins, signalling pathways, cellular processes, and diseases, in which serotonylation or, more general, monoaminylation is important.